THE SUBSTANTIAL EFFECT OF EDUCATIONAL RESOURCES AND FACILITIES IN ISLAMIC BOARDING SCHOOLS ON THE ENROLLMENT INTEREST OF NEW STUDENTS - Fatahillah Arrozi; Parmadi Zeki Ustad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
This study aims to empirically test the variables outlined in the research questions, specifically whether there is a significant relationship between educational facilities and infrastructure (X) and new student interest (Y). A simple random sample of 193 students was selected from a population of 450 students at SD Plus Al-Ishlah and SDN Taman 01 Bondowoso. Simple linear regression analysis was employed to analyze the data, using SPSS version 23 for statistical analysis. The results indicate a significant and positive influence of educational facilities and infrastructure on new student interest. This is supported by the calculated r-value being greater than the critical r-value (11.349 > 1.960). However, the coefficient of correlation is relatively low at 40.3%, suggesting that while there is a relationship, other factors may also contribute to new student interest. The level of significance is 5%. Therefore, the alternative hypothesis (Ha), which states that there is a significant and positive relationship between educational facilities and infrastructure and new student interest, is accepted.